Human Rights Enforcement Analysis In The Case Of Herry Wirawan Analysis Of Human Rights Enforcement In The Case Of Herry Wirawan - aprilia dwi santoso putri aprilia; Zakiya putri az-zahra zakiya (Universitas Duta Bangsa Surakarta, 2025)
This article analyzes the enforcement of human rights in the Herry Wirawan case, one of the most severe sexual crime cases in Indonesian history. Through normative juridical methods, this study examines the effectiveness of national and international human rights instruments in protecting children from sexual violence. The research reveals that while judicial procedures have been implemented fairly and sanctions applied firmly, significant weaknesses remain in prevention, early detection, and victim rehabilitation aspects. The findings indicate that although Indonesia possesses comprehensive human rights legal frameworks through various national legislations and ratified international conventions, their implementation still faces serious challenges, particularly in preventive and restorative aspects. This study recommends strengthening educational institution supervision systems, improving child-friendly reporting mechanisms, and providing comprehensive long-term rehabilitation programs for victims.